Work and well-being: collective and individual self-concept, job commitment, citizenship behavior, and autonomy as predictors of overall life satisfaction. Issue 4 (4th July 2022) - Roney, Christopher; Soicher, Hannah M.
ABSTRACT: A job may contribute to overall life satisfaction (LS) when it meets basic psychological needs. This study examined aspects of one's work (organizational commitment, citizenship behavior and autonomy), and individual differences in self-concept (collective versus individual), as predictors of overall LS. 295 employees working at a variety of jobs completed questionnaires online. Results showed that higher collective self-concept predicted greater LS; this was partially mediated by affective job commitment, work autonomy and altruistic citizenship behaviors, all of which also independently predicted greater LS. Higher individual self-concept was also a significant predictor of LS, partially mediated by compliance citizenship behaviors. These results suggest that when work fulfills a need for connectedness (i.e., for people with a collective self-concept), autonomy, and when we feel emotionally committed to our job, and go beyond what it requires, our overall LS is higher. These results clarify some positive ways that our work contributes to overall LS, but important questions remain for future research.